DESIGNING JOB ANALYSIS TO INCREASING EMPLOYEE PERFORMANCE IN KOPI ENCUS - Nurdin, Cuet Mutia Muhamad; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2018)
Abstract. Culinary industry is one of the strategic sectors for economic development in Indonesia. One of the culinary businesses that has become attractive for businessman and youngsters is coffee shop. Association of Indonesia Coffee Exporters and Industries (AICE) stated that coffee consumption in Indonesia is increasing every year (AICE, 2016). Kopi Encus is one of Bandung's cafe located in Sukajadi Street, Bandung. no clear rules about work distribution so employees faces unclear work while doing their work or unclear job description, because of that employee performance decreasing. To prevent that, job analysis is needed. Job analysis is used to obtain information about the job, which includes both job descriptions conducted in the workplace and the specificity of the skills required to perform the job. Job analysis can help Kopi Encus to create a system by managing job description and job specification. Conducting job analysis can make the employee know about their responsibilities clearly and avoid the overlapping. Therefore, the researcher did the job analysis in Kopi Encus to solve the problem. With more detail of job analysis, now Kopi Encus has detail job descriptions and job specifications, it can be used to clarify the function of the job so that with the explanation of the job function the employee will be able to do their job so that the employee performance increase.Keywords: Human resource management Job Analysis, Job Description, Job SpecificationÂ